Factor That Influencing Sustainability Performance in Cement Manufacturing Companies Listed on The Indonesia Stock - Fitri Anggra Eni; Merlyana Dwinda Yanthi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Digital technology rapid user growth over the years gives opportunity for new startup to join this market. In financial industry, cashless payment system become more popular and one of them is mobile wallet. Mobile wallet is gaining popularity during the Covid-19 pandemic and still growing until this day as a new mode of payment system due to it’s simplicity and QR-code based scan-to-pay method that gains millions of user in Indonesia. However, there is still some scepticism among users about it’s safety and merit that can cause hindrance on their intention to adopt it. Thus, this study intends to find out aspects that could trigger user intention on adapting Gopay, the most well known mobile wallet in Indonesia as a payment system. Extended-TAM model consist of perceived usefulness, perceived ease of use, and trust is used as a primary theory. Primary data is collected by an online-based survey to 114 respondents then analyzed with PLS-SEM (SmartPLS 4.1.0.2). The analysis indicate that perceived usefulness and trust impacts behavioral intention significantly, while perceived ease of use shows no influence towards behavioral intention.